2015
DOI: 10.1002/celc.201402456
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks: New Interlayer Dielectric Materials

Abstract: The design and synthesis of new interlayer dielectric (ILD) materials has been as ubjecto fi nterest in terms of their potential use in high-performance electronic devices.A ccording to Moore's law,t he number of active devices in an integrated circuit (IC) has been exponentially increasing, doubling approximately every 2years. [1] To keep pace with this rapidly advancing technology,t he performances of ICs can be enhanced by increasing transistor speed or reducing transistor size by packing more transistors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…The miniaturization of electronic devices in integrated circuits, means that new ultra‐low dielectrics as insulating material are required to decrease cross‐talk, signal delays, and power losses in electronic components. Recent theoretical studies have estimated the dielectric constants for a series of MOFs, and the calculated results show that many MOFs have promising electronic and dielectric properties . These theoretical studies also encouraged the related experimental works to further investigate and confirm the dielectric and optical properties for both crystalline MOFs and ZIFs, such as HKUST‐1, MIL‐53(Al), Zn‐based MOF and ZIF‐8 .…”
Section: Introductionmentioning
confidence: 92%
“…The miniaturization of electronic devices in integrated circuits, means that new ultra‐low dielectrics as insulating material are required to decrease cross‐talk, signal delays, and power losses in electronic components. Recent theoretical studies have estimated the dielectric constants for a series of MOFs, and the calculated results show that many MOFs have promising electronic and dielectric properties . These theoretical studies also encouraged the related experimental works to further investigate and confirm the dielectric and optical properties for both crystalline MOFs and ZIFs, such as HKUST‐1, MIL‐53(Al), Zn‐based MOF and ZIF‐8 .…”
Section: Introductionmentioning
confidence: 92%
“…By first‐principle DFT calculations, Warmbier et al subsequently showed that the κ values reported in were underestimated by less than 10%. As far as it is known, promising experimental evidence of κ lower than 2.5 is still infrequent, manifested only by: a) the 2.33(±0.05) value of κ reported for ZIF‐8 thin films at 10 5 Hz stored under ambient conditions with estimated ≈60% relative humidity; b) the 2.4 value shown at 10 5 Hz by pellets of [Sr(1,3‐BDC)] (1,3‐H 2 bdc = benzene‐1,3‐dicarboxylic acid); and c) the 1.2 and 2.1 values reported for films of MOF‐3 and MOF‐5 at 2 × 10 6 Hz, respectively . These authors claim that films of MOF‐5 are stable if exposed to water vapors, but they do not report κ measurements performed after exposure to humidity.…”
Section: Introductionmentioning
confidence: 99%
“…They provided a roadmap for the implementation of MOFs in microelectronics devices . A few reports on the dielectric behavior of MOFs as interlayer dielectrics components for integrated circuit design have also appeared . However, studies relating to the semiconducting behavior of MOFs are still in their initial stages, and further investigations are highly desired …”
Section: Introductionmentioning
confidence: 99%